2010
DOI: 10.1111/j.1467-8543.2009.00762.x
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Sharing through Face‐to‐Face Communication and Labour Productivity: Evidence from British Workplaces

Abstract: We investigate whether the adoption by workplaces of human resources management (HRM) practices that enhance face-to-face communication (FTFC) among employees is associated with productivity gains. The analysis is based on a nationally representative sample of over 500 British trading establishments drawn from the linked 2004 Workplace Employment Relations Survey and Annual Business Inquiry, for which objective measures of labour productivity (value added per employee) are available. We find a positive associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 45 publications
(77 reference statements)
1
6
0
Order By: Relevance
“…Labor productivity. Drawing on prior research (Salis & Williams, 2010), we measure labor productivity as the logarithm of firm's value added, divided by the number of employees. Value added was measured in 2008 and is recorded in the ESANE database; the number of employees is obtained from the COI database.…”
Section: Methodsmentioning
confidence: 99%
“…Labor productivity. Drawing on prior research (Salis & Williams, 2010), we measure labor productivity as the logarithm of firm's value added, divided by the number of employees. Value added was measured in 2008 and is recorded in the ESANE database; the number of employees is obtained from the COI database.…”
Section: Methodsmentioning
confidence: 99%
“…This method aids workers in responding fast, making choices, and coming up with innovative ideas and solutions to increase client happiness (Haas and Hansen, 2007;Feng et al, 2005;Olander et al, 2016;Martinkenaite, 2011). Salis and Williams (2010) prove that applying human resource management practices to share knowledge can increase employee productivity. Internal and external information exchange has a considerable positive impact on work productivity, as demonstrated by Aboelmaged (2018).…”
Section: Affective Knowledge Sharing and Knowledge-worker Productivitymentioning
confidence: 99%
“…Work structure, task division, organizational decision-making, clarity of job descriptions, collaboration, information-sharing activities, delays and hold-ups, and the ability to influence one's work are all variables in the work process that affect knowledge workers' productivity (Antikainen and Lonnqvist, 2006). Salis and Williams (2010) prove that applying human resource management practices to share knowledge can increase employee productivity. Supporting this, Aboelmaged (2018) also proves that sharing internal and external knowledge impacts work productivity significantly.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies, indeed, have highlighted the importance of in-person interactions for physical, psychological and social wellbeing [14][15][16][17]. In particular, observational, interviewbased and questionnaire-based studies have found that in workplaces face-to-face interactions are associated with increased trust and improved communication among employees, efficient problem solving and a positive effect on the overall organization knowledge diffusion, innovation ability and performance [18][19][20][21]. Similar results have been also found using wearable sensors to study face-to-face interactions and their effect on productivity, performance and complex tasks' completion [22][23][24].…”
Section: Introductionmentioning
confidence: 99%